Editorial Contexts of teaching and professional learning - Flores, Maria Assunção (2016)
Understanding the nature and purpose of teaching and learning entails not only the analysis of its conceptual and epistemological dimensions but also the consideration of the social, political, cultural and economic contexts in which they are embedded. A look at existing international literature on teaching and learning reveals some common trends, for example, growing emphasis on issues of accountability and outcome-led orientation, but also diverse modes of government intervention, different strategies and learning environments, and various understandings of assessing and improving teaching and learning quality (Darling-Hammond, Newton, & Wei, 2010; Eilam & Poyas, 2009; Flores, 2011; Ludlow et al., 2010). The complexity of teaching in challenging times, the process of learning to teach, the nature of teacher professional knowledge, the core characteristics of good teaching, the provision of relevant contexts for teaching and learning, etc. are issues that have engaged researchers and policy-makers worldwide to respond to the social, cultural and political demands and transformations in society.